Problematika Penyusunan Kamus Bahasa Indonesia Dalam Pembaruan Kosakata Di Kamus Besar Bahasa Indonesia - Tia Maharani; Anggi Nur Febriani; Hoirina Pulungan; Safira Ayesha Ismaidini; Nurul Aisyah Syahkila; Nurul Azizah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The Indonesian language continues to evolve alongside advances in technology, science, and digital communication. This has given rise to a variety of new vocabulary terms used by the public in their daily lives. The Kamus Besar Bahasa Indonesia (KBBI), as the standard dictionary of the Indonesian language, plays a crucial role in documenting and establishing the meanings and usage of these terms. This study aims to examine the challenges in the process of updating vocabulary in the KBBI and to identify solutions that can be applied in modern lexicography systems. The research method used is qualitative descriptive, employing a literature review of various journals and scientific sources relevant to lexicography and language development in the digital age. The results of the study indicate that vocabulary updates in the KBBI face several challenges, such as the rapid evolution of vocabulary on social media, the lack of a representative language corpus, and the influence of foreign languages and regional dialects. To address these issues, it is necessary to strengthen a digital corpus-based lexicography system, develop new vocabulary databases, and implement an observation process for vocabulary before it is included in the dictionary. These efforts are expected to improve the quality of vocabulary updates in the KBBI so that the dictionary remains relevant to the development of the Indonesian language in society.